2009
DOI: 10.1210/en.2009-0213
|View full text |Cite
|
Sign up to set email alerts
|

Brain-Derived Neurotrophic Factor Promotes Implantation and Subsequent Placental Development by Stimulating Trophoblast Cell Growth and Survival

Abstract: Successful implantation of the blastocyst and subsequent placental development is essential for reproduction. Expression of brain-derived neurotrophic factor (BDNF) and neurotrophin-4/5, together with their receptor, tyrosine kinase B (TrkB), in trophectoderm cells of blastocyst suggests their potential roles in implantation and placental development. Here we demonstrated that treatment with BDNF promoted blastocyst outgrowth, but not adhesion, in vitro and increased levels of the cell invasion marker matrix m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
104
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(110 citation statements)
references
References 45 publications
3
104
0
3
Order By: Relevance
“…5 In the present work we focus our analysis on another popular gene in behavioral genetics, highly important in neurodevelopment and in system-level neural phenotypes and sensitive to environmental factors, the gene coding for the Brain Derived Neurotrophic Factor (BDNF). BDNF is a highly regulated protein, a crucial factor for the development of the feto-placental unit 6 and of the brain, 7 as well as for neural plasticity, energy metabolism, learning, episodic and working memory (WM) [7][8][9][10][11][12] and cancer. 13 The effects of BDNF on synaptic plasticity and neuron survival strongly suggest a role for this factor in schizophrenia, a neurodevelopmental disorder whose risk is heritable and characterized by physiological prefrontal cortex (PFC) dysfunction during WM, [14][15][16] as well as reduced prefrontal levels of BDNF.…”
Section: Introductionmentioning
confidence: 99%
“…5 In the present work we focus our analysis on another popular gene in behavioral genetics, highly important in neurodevelopment and in system-level neural phenotypes and sensitive to environmental factors, the gene coding for the Brain Derived Neurotrophic Factor (BDNF). BDNF is a highly regulated protein, a crucial factor for the development of the feto-placental unit 6 and of the brain, 7 as well as for neural plasticity, energy metabolism, learning, episodic and working memory (WM) [7][8][9][10][11][12] and cancer. 13 The effects of BDNF on synaptic plasticity and neuron survival strongly suggest a role for this factor in schizophrenia, a neurodevelopmental disorder whose risk is heritable and characterized by physiological prefrontal cortex (PFC) dysfunction during WM, [14][15][16] as well as reduced prefrontal levels of BDNF.…”
Section: Introductionmentioning
confidence: 99%
“…Kawamura et al [16] found BDNF could promote blastocyst development by increasing total cell numbers in blastocysts and inhibiting trophectoderm cells apoptosis. In another study, they demonstrated that BDNF could improve fetal growth by increasing trophoblast cell growth and survival during implantation and subsequent placental development through a certain autocrine or paracrine mechanism of modulation [17].…”
Section: Discussionmentioning
confidence: 99%
“…Par exemple, il semble impliquĂ© dans la rĂ©gulation de l'homĂ©o-stasie glucidique, mais aussi dans les processus liĂ©s Ă  l'angiogenĂšse [3]. La dĂ©couverte de l'expression du systĂšme BDNF/TrkB dans le placenta [4] suggĂ©-rait son implication dans le dĂ©veloppe-ment placentaire et foetal, ce qui a, de fait, Ă©tĂ© dĂ©montrĂ© rĂ©cemment.…”
Section: Biologie Du Bdnfunclassified
“…Le rĂ©cepteur TrkB est, quant Ă  lui, exprimĂ© dans le trophospongium mais aussi dans la zone labyrinthique qui constitue la principale zone d'Ă©change vasculaire foeto-maternelle [4,5]. Une Ă©tude combinant des expĂ©rimentations menĂ©es in vitro et in vivo chez des souris vient de dĂ©montrer l'importance du BDNF dans le dĂ©velop-pement placentaire et foetal.…”
Section: Bdnf Et Gestationunclassified
See 1 more Smart Citation